Transformation of Creative Thinking Skills and Environmental Concern with PBSL Learning in Geography Class - Dewi Nur Azizah; Sumarmi Sumarmi; Purwanto Purwanto; Yusuf Suharto; Fajar Wulandari (JETL (Journal of Education, Teaching and Learning), 2025)
The ability to think creatively is an important skill that must be possessed by 21st century students, while an attitude of caring for the environment is an important foundation in maintaining the balance of nature. This study aims to: (1) measure the influence of Project Based SCAMPER Learning (PBSL) on students' creative thinking skills, and (2) evaluate the influence of PBSL on environmental care attitudes. This research was conducted at SMAN 1 Ngadiluwih with a sample of students in class X, consisting of 36 students in the experimental class and 36 students in the control class. Data were collected using creative thinking skills tests and environmental care questionnaires, and analyzed using statistical tests, including normality, homogeneity, and two-way ANOVA tests. The results show that PBSL has a significant impact on students' creative thinking skills, especially on the originality indicator, which has experienced the greatest improvement. Students are able to produce innovative new ideas in the field of education.